Considerations and implications of current in vitro model systems to study optic nerve head cellular mechanobiology - Strat, Ana N.; Ganapathy, Preethi S. (Frontiers in Cell and Developmental Biology, 2025)
The optic nerve head (ONH) is a primary site of biomechanical strain within the eye. Here, tensile, compressive and shear forces can impact both physiologic function and pathologic dysfunction of the tissue. Under healthy conditions, the ONH can withstand dynamic fluctuations in intraocular pressure (IOP), which is the main driver of biomechanical strain. In glaucoma, pathologic biomechanical strains lead to disrupted cellular homeostasis, increased ECM remodeling and fibrosis, loss of retinal ganglion cells (RGCs), and irreversible blindness. In vitro model systems are increasingly used to dissect the mechanisms by which ONH cells respond to biomechanical strain (i.e., their mechanobiology). This review aims to present the current state of these in vitro model systems. Traditional two-dimensional (2D) stretch systems have provided important insights into ONH cellular mechanobiology. More recent 3D in vitro models include hydrogel-based systems that incorporate natural or synthetic ECM polymers that support development of cell morphology and ECM interactions similar to those observed in vivo; these models permit application of compressive and tensile biomechanical strain. This review also discusses ONH biomechanical strains as they pertain to glaucoma pathophysiology, the ONH cell types implicated in pathologic mechanobiology, and the experimental parameters generally used in current in vitro systems. Ultimately, refinements of these in vitro model systems can provide crucial mechanistic insights into cellular mechanodysfunction and potential therapeutic targets for glaucoma.